The role and importance of automatic translation programs for the Uzbek language - Komilova, Zulkhumor Khokimovna; Hoshimova, Gulsanam (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the current role and importance of modern automatic translation programs for the Uzbek language. Automatic translation systems are based on artificial intelligence and neural networks, and the importance of taking into account the morphological and syntactic features of the Uzbek language is demonstrated.